Exploring the nexus of water insecurity and psychological distress in Windhoek's informal settlements, Namibia - Tobias Willem Shinyemba; Khanyisile Cloete (IWA Publishing, 2023)
Water insecurity has long been a pressing issue, particularly in the informal settlements of Windhoek. The current study aims to investigate the relationship between water insecurity and residents' psychological distress in Windhoek's informal settlements. The study draws upon secondary data collected by Future Resilience for African Cities and Lands in 2017. Confirmatory factor analysis was used to establish the relationship between water insecurity, psychological distress, and three manifest variables (source of income, housing type, and household structure). The study findings revealed a positive association between housing type and psychological distress (β = 0.056, p < 0.001). Household structure was negatively associated with psychological distress (β = −0.035, p < 0.001) and water insecurity (β = −0.054, p < 0.001). In addition, a positive association (β = 0.595, p < 0.001) was found between water insecurity and psychological distress, suggesting that water scarcity negatively impacts residents' mental well-being. The study highlights the need to address the issue of water insecurity in informal settlements across Windhoek. This can be achieved by setting measures to make water and essential sanitation services more accessible and affordable to residents in these communities. Such approaches would help mitigate the effect of water insecurity on the psychological distress of persons living in informal settlements and create more resilient and sustainable settlements. HIGHLIGHTS Approximately 78.8% of the interviewed households lived in shacks.; Fetching water from neighbours owing to water shortages in certain households accounted for around 64.2% of variation in water insecurity.; Water insecurity was negatively related to household structure.; There was a negative relationship between psychological distress and household structure.;